2001
DOI: 10.1253/jcj.65.129
|View full text |Cite
|
Sign up to set email alerts
|

Transient but Marked ST Elevation in Precordial Leads Caused by Ischemia of the Isolated Right Ventricular Branch

Abstract: n coronary artery disease, transient ST elevation in precordial leads generally indicates anteroseptal ischemia. However, there are some cases where occlusion of a side branch during percutaneous transluminal coronary angioplasty (PTCA) of the proximal right coronary artery has induced right ventricular infarction and precordial ST elevation. [1][2][3][4] Right ventricular infarction usually accompanies inferior wall infarction, and rarely occurs alone, with such cases accounting for only about 3% of all cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Van der Bolt et al Observed that isolated acute occlusion of the RV branch after angioplasty could be followed by ST segment elevations in leads V1 to V3 [8]. Sonoda et al have reported that ST segment elevation in the precordial leads occurred in a reproducible manner when the balloon occluded the RV branch [9]. Hence, our case confirms previous studies and observations that ST segment elevation in precordial leads V1 to V4 may be a rare sign of RV branch occlusion.…”
Section: Right Ventricular Myocardial Infarction (Mi) Is Normallysupporting
confidence: 89%
See 1 more Smart Citation
“…Van der Bolt et al Observed that isolated acute occlusion of the RV branch after angioplasty could be followed by ST segment elevations in leads V1 to V3 [8]. Sonoda et al have reported that ST segment elevation in the precordial leads occurred in a reproducible manner when the balloon occluded the RV branch [9]. Hence, our case confirms previous studies and observations that ST segment elevation in precordial leads V1 to V4 may be a rare sign of RV branch occlusion.…”
Section: Right Ventricular Myocardial Infarction (Mi) Is Normallysupporting
confidence: 89%
“…Hence, our case confirms previous studies and observations that ST segment elevation in precordial leads V1 to V4 may be a rare sign of RV branch occlusion. This explains that, from an electrocardiographic perspective, RV MI may occur also because of isolated RV branch occlusion in the absence of inferior electrocardiographic changes [9,10].…”
Section: Right Ventricular Myocardial Infarction (Mi) Is Normallymentioning
confidence: 99%
“…The Brugada-type ST shift has been identified in various cardiac and non-cardiac diseases, such as myocardial ischemia, 6,7 arrhythmogenic right ventricular cardiomyopathy 8 and accidental hypothermia. 9 Despite marked ECG abnormalities, myocardial cell damage, coronary hypoperfusion, coronary artery spasm, myocarditis, pericarditis or cardiomyopathy were not evident in the present case.…”
Section: Discussionmentioning
confidence: 99%